Integration of Data Visualization Technologies and Artificial Intelligence in Media (Herald of Journalism, 2025)
Modern media are actively implementing digital technologies, including artificial intelligence (AI), and data visualization has become an important part of journalism, allowing to effectively present complex information to the audience. At the same time, Kazakhstani and Russian publications are just beginning to master these approaches, which makes their comparison with international practices especially relevant. The purpose of this study is to analyze and compare the practices of using data visualization and AI in the media of Kazakhstan, Russia, and other countries. The work applies to the methods of comparative analysis and content analysis of media materials.The study revealed that the use of data visualization and AI in Kazakhstani media is limited, in Russian media these technologies are used more often, and international media demonstrate the highest level of their integration. The scientific novelty of the work lies in the fact that for the first time a comprehensive classification of forms of data visualization using AI has been proposed, which expands the theoretical understanding of digital tools in journalism. The practical significance of the results is that the proposed conclusions and approaches can help Kazakhstani media improve visual content and increase the effectiveness of interaction with the audience. Thus, the conducted analysis reflects the multi-level implementation of innovations in the field of journalism and points to ways to reduce the gap between domestic and global media practices.
Keywords: data visualization, artificial intelligence, media, journalism, comparative analysis.